Nanoscale characterization of dynamic cellular viscoelasticity by atomic force microscopy with varying measurement parameters. (June 2018) - Li, Mi; Liu, Lianqing; Xu, Xinning; Xing, Xiaojing; Dang, Dan; Xi, Ning; Wang, Yuechao
Abstract: Cell mechanics plays an important role in regulating the physiological activities of cells. The advent of atomic force microscopy (AFM) provides a novel powerful instrument for quantifying the mechanics of single cells at the nanoscale. The applications of AFM in single-cell mechanical assays in the past decade have significantly contributed to the field of cell and molecular biology. However, current AFM-based cellular mechanical studies are commonly carried out with fixed measurement parameters, which provides limited information about the dynamic cellular mechanical behaviors in response to the variable external stimuli. In this work, we utilized AFM to investigate cellular viscoelasticity (portrayed as relaxation time) with varying measurement parameters, including ramp rate and surface dwell time, on both cell lines and primary cells. The experimental results show that the obtained cellular relaxation times are remarkably dependent on the parameter surface dwell time and ramp rate during measurements. Besides, the dependencies to the measurement parameters are variable for different types of cells, which can be potentially used to indicate cell states. The research improves our understanding of single-cell dynamic rheology and provides a novel idea for discriminating different types of cells by AFM-based cellular viscoelastic assays with varying measurement parameters.